Self Esteem in Adolescent Smokers at South Tangerang in 2021 - Ina Annisa; Hanifah Ismi; Khairunnisa Khairunnisa; Lingga Rizarni; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Smoking behavior is an activity where someone uses cigarettes. One of the factors that influence smoking habits in adolescents is to increase self-esteem. The purpose of this study was to obtain information about self-esteem in adolescent smokers at South Tangerang in 2021. The research method is descriptive using a qualitative study design. The sample in this study were four adolescent active smokers with an age range of 19 – 23 years who came from different universities by conducting in-depth interviews and conducting document reviews. This interview transcript was evaluated using content analysis, namely a one-by-one analysis of the pure interview results. The results of the interview showed that the informant felt the physical influence or the symptoms felt, namely coughing and enjoyed. Informants do not consider smoking behavior to increase self-confidence, but relationships and interactions in the family are considered the most valuable, valuable, and important for the development of individuals as members. Smoking can be a way for teenagers to look free and mature when they adjust to their smoking peers even though smoking can encourage the emergence of diseases that can lead to death. Based on this, it can be concluded that smoking behavior does not affect a person's level of self-confidence (self-esteem). Smoking can also encourage the emergence of types of diseases that can lead to death because smoking will release about 4,000 chemical components which not only affect active smokers but also those around them who feel the dangers of passive smokers.